Adsorption of Congo red from water with spindle-like boehmite: the role of lattice plane (020). Issue 14 (28th January 2016) - Li, Guangci; Sun, Yuanyuan; Li, Xuebing; Liu, Yunqi
Abstract : Spindle-like boehmite with a highly efficient adsorption performance for Congo red (CR) from water is prepared via a hydrothermal process, and the adsorption rate of CR strongly depends on the lattice plane (020) of boehmite crystallites. Abstract : Spindle-like boehmites with high adsorption capacity for Congo red (CR) from water were prepared via a hydrothermal synthesis method without any surfactants. The crystallite sizes of boehmites can be subtly adjusted by hydrothermal post-treatment for various durations, and the crystalline structure, morphology and textural properties of boehmites were characterized by different techniques. The adsorption capacities and rates of CR onto boehmites were thoroughly evaluated with the help of equilibrium and kinetics experiments. The adsorption isotherms are fitted well to the Langmuir equation, and the Langmuir adsorption capacity ( q max ) is as high as 427.4 mg g −1 . The kinetics data show that the adsorption process can be well described by pseudo-second-order kinetics model, and besides, adsorption rate is closely related to the exposed surface area of lattice plane (020) of boehmite crystallite, because this plane has a relatively high OH density that is favourable to the adsorption of CR. The IR characterization and the relationship between the pH values of the zero point of charge (pHzpc ) for different boehmites and adsorption behavior of CR suggest that the involved adsorption process is driven by the hydrogen bonding and electrostatic attraction at the same time.